Emissions required to close the decent living gaps in Chinese city clusters - Li, Mo; Hong, Yuezhang (Frontiers in Environmental Science, 2025)
Effective demand-side mitigation requires a shift from growth-driven to sufficiency-driven consumption. Decent living standards (DLSs) serve as practical indicators for achieving distributive justice in demand-side mitigation policies. The concept has gained momentum due to its advances in addressing carbon inequality and promoting social justice. In China, DLSs remain deprived in hinterland cities and are excessively satisfied in central cities. By translating DLSs into city-level context-specific scenarios, this study assesses the avoided emissions that would have occurred from 2017 to 2050 under two DLS scenarios. We found that leveraging DLSs for all does not lead to an increase in national carbon emissions. A novel indicator of DLS deprivation, the decent living gap (DLG), was proposed to address city-level inequalities and guide redistributions among city clusters. Central cities need to contribute 33% toward closing the national DLG, with some cities needing to contribute as much as 69%. For high-income city clusters, 86% of their DLG is expected to be met through imports from lower-income city clusters. This DLG import will significantly reduce the mitigation burden of less developed regions. Our study provides valuable insights into equitable demand-side mitigation pathways that ensure DLSs for all.